Inﬂuence of diﬀerent parameters on the characteristics of hazelnut (var. Grada de Viseu) grown in Portugal - Ferrão, Ana Cristina (2022)
"Grada de Viseu” is an indigenous hazelnut variety from Portugal, and it is considered by the producers as the most important variety in terms of production and productivity. Therefore, the aim of this study was to assess the in ﬂ uence of harvest year ( 2017/2018/2019 ) and location of production ( Viseu/Faia ) on some physical and chemical properties of the variety “ Grada de Viseu, ”namely biometric parameters, colour, true and bulk densities, texture parameters ( hardness and friability ) , and chemical composition. The results showed that the fruitsof the samples harvested in 2019 had higher values of height, width, and thickness. Hazelnuts from 2018 had a clearer shell, independently of the location of production, but only the samples from Faia harvested in 2018 had a clearer kernel. As for the texture, the fruits grown in Viseu harvested in 2018 had a harder shell and was more resistant to fracture, whereas the sample from 2019 had a harder kernel. In all cases, fat was the major chemical component. The sample from 2019 had a water activity greater than 0.62, meaning that its stability was not guaranteed. “ Grada de Viseu ” from Faia in 2018 presented a higher induction period and, therefore, was the one with the highest oxidation stability. The year of production showed to be the best predictor for almost every chemical and biometric characteristics. In general, it was possible to verify that harvesting year and geographical location in ﬂ uence hazelnut characteristics.